ANALISIS INDEPENDENSI DEWAN KOMISARIS, EFEKTIVITAS KOMITE AUDIT, DAN KUALITAS AUDIT TERHADAP PRAKTIK MANAJEMEN LABA PERUSAHAAN (Studi Empiris pada Perusahaan Non-Finansial yang Terdaftar di Bursa Efek Indonesia Tahun 2016-2019) - Febrina Claudya Tambunan; Etna Nur Afri Yuyetta (Diponegoro Journal of Accounting, 2021)
The interaction between corporate governance mechanisms and earnings management practices is an important topic which must be analyzed deeply. This study examines the effect of corporate governance mechanisms in reducing earnings management practice. The corporate governance mechanisms included in this study are Board of Commissioner, Audit Committee, and Audit Quality.According to Agency Theory concerning about Agency Problem Type II, this study examines hypothesis about the relationship between corporate governance mechanisms and earnings management. Board of Commissioner is measured by Board of Independence Commissioner percentage. Audit Committee is measured by forming a score the number of audit committee’s meetings and the number of members formed an audit committee. Audit quality is measured by auditor’s reputation and auditor tenure.The sample of this study was obtained using purposive sampling method with the result that 126 samples of non-financial company listed on the Indonesia Stock Exchange for a year, and total of samples are 504 samples for 2016-2019. This study uses a multiple regression analysis. Statistical technique used in this study is panel data. The result of this study is corporate governance mechanisms, especially board of commissioner and audit committee, have significant association with earnings management practices.